The Dynamics of Terrorism and International Criminal Law - Ogbe, Richard Suofade (ABUAD Law Journal, 2023)
This paper seeks to analyse and showcase the contemporary applicable prevailing developments vis-a-vis the concept of terrorism under international criminal law. It showcases the jurisprudence for the criminalization of terrorism under international criminal law. This paper further seeks to critique the advancement of the idea of terrorism in international law and highlights some contemporary developments with emphasis on aspects relevant to international criminal law.This paper equally seeks to analyze the fundamental distinction between terrorism as a treaty crime and terrorism as an international crime.One intriguing problem is a generally accepted definition and structuralexponential concern and analysis of terrorism under universal jurisprudence. Despite the problems of definition and distinction, the contemporary generally accepted trend is the criminalisation of international terrorism in any form or structure to guarantee international peace and security.